Reduction of p11 in dorsal raphe nucleus serotonergic neurons mediates depression-like behaviors - Wei Li; Zuqi Shen; Xuan Yin; Weiqi Chang; Xiaorong Chen; Jin Yu; Shifen Xu (Translational Psychiatry, 2023)
Abstract The pathology of depression is related to the imbalance of various neurotransmitters. The dorsal raphe nucleus (DRN), the main brain region producing 5-HT, is crucially involved in the pathophysiology of depression. It contains several neuron types, in which GABAergic neurons are activated by stimuli associated with negative experiences and 5-HT neurons are activated by reward signals. However, little is known about its underlying molecular mechanisms. Here, we found that p11, a multifunctional protein associated with depression, was down-regulated by chronic social defeat stress in 5-HTDRN neurons. Knockdown of p11 in DRN induced depression-like behaviors, while its overexpression in 5-HTDRN neurons alleviated depression-like behavior caused by chronic social defeat stress. Further, p11 regulates membrane trafficking of glutamate receptors in 5-HTDRN neurons, suggesting a possible molecular mechanism underlying the participation of p11 in the pathological process of depression. This may facilitate the understanding of the molecular and cellular basis of depression.